Music listening habits of adolescents in a South Indian city (Bangladesh Journal of Medical Science, 2023)
Objective: Universal access to personal music listening devices has attracted many adolescents to listen to music. However, risky music listening behavior can lead to music-induced hearing loss, becoming a major social and public health problem. We aimed to investigate music listening habits in three groups of adolescents based on age, learn the differences in music listening habits among the groups, if any, and assess their knowledge regarding loud music-induced hearing loss.Materials and method: A total of 300 adolescents aged 13-20 years studying in various schools and colleges of a South Indian city completed a questionnaire to understand music listening habits and knowledge regarding loud music-induced hearing loss. Based on age and education level, they were divided into three groups of 100 each [high school(HS): 13-16 years, pre-university(PU): 16-17 years, and undergraduate(UG) level: 18-20 years].Results: Duration and frequency of music listening, usage of the device, and accessory were similar among the three groups. However, across the age, there is a difference in the loudness in music listening (younger HS and PU groups frequently used loud volume) and the awareness about the damage caused to hearing due to loud music (younger HS group was least aware). A reduced hearing was reported by 17% of the UG group as opposed to 4% of the HS group.Conclusion: With the use of earphones and loud volume, younger adolescents are at greater risk for music-induced hearing loss than older adolescents. This group, if educated, is ready to accept modifications in listening behaviors that are hearing protective.Bangladesh Journal of Medical Science Vol. 22 No. 04 October’23 Page : 882-894